Male inmate-on-inmate sexual assault: characteristics associated with risk - Sutton, Jessica (Criminology, criminal justice, law & society, 2016)
Sexual assault in prisons has received sporadic attention from researchers overthe years, though The Prison Rape Elimination Act (PREA) of 2003 has drawn more attention to this problem in the past decade. This study contributes to the growing and more recent literature on characteristics associated with risk for sexual assault in prison. By using unique data and a novel analytic strategy, we examined perpetrator and victim characteristics associated with male inmate-on-inmate sexual assault. Whereas most studies of prison sexual assault have relied on victim data, we examined both perpetrator and victim data for all founded inmate-on-inmate sexual assaults that occurred in the Ohio prison system during a four year period. We compared perpetrators to victims, and both perpetrators and victims to a comparison group that was representative of the general prisoner population. This approach has not previously been used to our knowledge, and we found a number of clear patterns distinguishing perpetrators and victims from each other and from the comparison group.